Christmas at the Royal Institution : An anthology of lectures - James, Frank A. J. L; Faraday, M; Tyndall, J; Ball, R S (Singapore World Scientific Publishing Company, 2007)
This book is an anthology of 11 Christmas lectures delivered at The Royal Institution from the 1860s to the 1990s. Aimed at inspiring young audiences, these lectures by renowned scientists-including Michael Faraday and Lawrence Bragg-have played a key role in promoting science to the public. Broadcast and published globally, they reflect the evolution of science communication over more than a century. The collection offers insight into how scientific ideas have been shared and celebrated through generations.
Includes bibliographical references and index
Keywords: Tham khảo